Oral manifestations in chikungunya patients: A systematic review. - Daniela Brostolin da Costa; Alessandro Diogo De-Carli; Livia Fernandes Probst; Antonio José Grande; Ana Tereza Gomes Guerrero (Public Library of Science (PLoS), 2021)
Background Chikungunya fever is considered an abrupt onset arbovirus transmitted by mosquitoes, mainly Aedes aegypti and Aedes albopictus. The disease has a significant impact on the quality of life of affected persons, and many of its numerous symptoms have not yet been properly clarified, such as the manifestations that can occur in the oral cavity. The aim of this study was to identify the main oral manifestations related to chikungunya fever, as well as describe the demographic characteristics of patients, by conducting a systematic review of the literature. Methods and findings Searches were performed in MEDLINE (PubMed), Embase (Elsevier), LILACS (VHL), Cochrane Library, Scopus, and CAPES electronic databases for theses and dissertations published up to January 16, 2021 without language and date restrictions. Additional manual searches of gray literature, reference list, and Google Scholar were carried out. We included 27 studies highlighting mainly oral manifestations that cause masticatory discomfort such as ulcers and oral thrush, gingival bleeding, pain and burning of the oral mucous membranes, temporomandibular joint (TMJ) arthralgia, opportunistic infections, and changes in taste. Conclusions There seems to be a predominance of oral manifestations that cause discomfort when chewing, such as ulcerations in the acute phase of the disease, with complete remission within 3 to 10 days after the onset, apparently mostly affecting women and older persons. These oral manifestations can be compatible with basic viral infections related to inflammatory response and transitory immunosuppression.